Delo kot vsako drugo in hkrati kot nobeno drugo - Hrženjak, Majda (Socialno delo, 2015)
While after the World War II, paid care work in private households has almost disappeared because of the rising welfare systems, in last decades it is again in steep increase all over the Europe given the restructuring of the role of state in social reproduction which leads to individualization and reprivatisation of care work. This work is marked by multiple peculiarities such as: location in private sphere of households; fragmentation, flexibilisation and informalization; feminization and etnicization; social devaluation, and at the same time it has no clear status in modern labour legislation. The article analyzes selected transnational and national strategies, including the Slovenian one, which promote regulation of home based care work from the perspectives of quality of employments and care services.
Keywords: care regimes; skrbstveno delo; neplačano delo; unpaid work; spol; gender; trg dela; labour market; zakonodaja; policies; siva ekonomija; grey economy; European Union; Evropska unija; Slovenia; Slovenija